Emerging technologies for food processing (Elsevier Academic Press, 2005)
Emerging Technologies for Food Processing presents a comprehensive review of innovations in food processing, stresses topics vital to the food industry today, and pinpoints the trends in future research and development. This volume contains 27 chapters and is divided into six parts covering topics such as the latest advances in non-thermal processing, alternative technologies and strategies for thermal processing, the latest developments in food refrigeration, and current topics in minimal processing of vegetables, fruits, juices and cook-chill ready meals and modified atmosphere packaging for minimally processed foods